2005
DOI: 10.1074/jbc.m502937200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Intra- and Intermolecular Disulfide Bridges in the Multidrug Resistance Transporter ABCG2

Abstract: ABCG2 is an ATP binding cassette (ABC) half-transporter that plays a key role in multidrug resistance to chemotherapy. ABCG2 is believed to be a functional homodimer that has been proposed to be linked by disulfide bridges. We have investigated the structural and functional role of the only three cysteines predicted to be on the extracellular face of ABCG2. Upon mutation of Cys-592 or Cys-608 to alanine (C592A and C608A), ABCG2 migrated as a dimer in SDS-PAGE under non-reducing conditions; however, mutation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 28 publications
3
120
2
Order By: Relevance
“…Cysteine residues that are potentially disulfide bridged do not participate in the structure of putative MCT8 protomer interface(s) in oligomers (Visser et al 2009), as has been reported, for example, for GPCRs (Berthouze et al 2007) and other members of the MFS (Hastrup et al 2003, Henriksen et al 2005. Moreover, it has been demonstrated that the amino acids from positions 267 to 360 (putative TMH4-6) are not involved in MCT8 protomer contacts (Visser et al 2009).…”
Section: Transporter Oligomers and Structure-function Relationshipsmentioning
confidence: 73%
“…Cysteine residues that are potentially disulfide bridged do not participate in the structure of putative MCT8 protomer interface(s) in oligomers (Visser et al 2009), as has been reported, for example, for GPCRs (Berthouze et al 2007) and other members of the MFS (Hastrup et al 2003, Henriksen et al 2005. Moreover, it has been demonstrated that the amino acids from positions 267 to 360 (putative TMH4-6) are not involved in MCT8 protomer contacts (Visser et al 2009).…”
Section: Transporter Oligomers and Structure-function Relationshipsmentioning
confidence: 73%
“…Dimerization is not essential for membrane localization and transport activity since treatment with mercaptoethanol, a reducing agent, did not affect the ATP-dependent transport of methotrexate by ABCG2 [54]. Furthermore, substitution of alanine for cysteine 603 did not affect membrane localization and resistance to mitoxantrone, although it abolished dimerization [24]. It should be noted that, recently, higher forms of oligomers (tetramer and dodecamer) of ABCG2 have been suggested, in which a homodimer linked by a disulfide bond is the minimum unit [84].…”
Section: Abcg2 (Bcrp/abcp/mxr)mentioning
confidence: 99%
“…ABCG2 has three preserved cysteine residues (592, 603, and 608) in the large extracellular loop between putative transmembrane domain 5 and 6. Among these residues, cysteine 603 is involved in the formation of an intermolecular disulfide bond, whereas the others have been suggested to form an intramolecular disulfide bond [24]. Dimerization is not essential for membrane localization and transport activity since treatment with mercaptoethanol, a reducing agent, did not affect the ATP-dependent transport of methotrexate by ABCG2 [54].…”
Section: Abcg2 (Bcrp/abcp/mxr)mentioning
confidence: 99%
“…For several other membrane proteins that are able to form multimers, oligomerization was shown to be a prerequisite for the export from the ER and for correct PM targeting (Gao and Dean, 2000;Liang et al, 2004;Salahpour et al, 2004). Intra-and intermolecular disulfide bridges together were shown to be important for the structure and functions of the human multidrug resistance transporter ABCG2 (Henriksen et al, 2005). In mitochondria, a disulfide relay system catalyzes the import of proteins into the intermembrane space by an oxidative folding mechanism (Mesecke et al, 2005), and for immunoglobulins free thiol groups play a role in the transport through the secretory pathway and the quality control (Alberini et al, 1990;Fra et al, 1993).…”
Section: Redox Control Of Membrane Protein Targetingmentioning
confidence: 99%